No evidence of pathological autoimmunity following Mycobacterium leprae heat-shock protein 65-DNA vaccination in mice - Lima, D. S.; Zárate-Bladés, C. R.; Souza, P. R.M.; Trombone, A. P.; Santos, R. R. [UNESP]; Brandão, I. T.; Masson, A. P.; Bonato, V. L.; Coelho-Castelo, A. A.M.; Sartori, A. [UNESP]; Vendramini, M.; Soares, E. G.; et al. (SAGE Publications, 2009)
Heat-shock proteins (HSPs) are currently one of the most promising targets for the development of immunotherapy against tumours and autoimmune disorders. This protein family has the capacity to activate or modulate the function of different immune system cells. They induce the activation of monocytes, macrophages and dendritic cells, and contribute to cross-priming, an important mechanism of presentation of exogenous antigen in the context of MHC class I molecules. These various immunological properties of HSP have encouraged their use in several clinical trials. Nevertheless, an important issue regarding these proteins is whether the high homology among HSPs across different species may trigger the breakdown of immune tolerance and induce autoimmune diseases. We have developed a DNA vaccine codifying the Mycobacterium leprae Hsp65 (DNAhsp65), which showed to be highly immunogenic and protective against experimental tuberculosis. Here, we address the question of whether DNAhsp65 immunization could induce pathological autoimmunity in mice. Our results show that DNAhsp65 vaccination induced antibodies that can recognize the human Hsp60 but did not induce harmful effects in 16 different organs analysed by histopathology up to 210 days after vaccination. We also showed that anti-DNA antibodies were not elicited after DNA vaccination. The results are important for the development of both HSP and DNA-based immunomodulatory agents. Copyright © by BIOLIFE, s.a.s.
Keywords: Autoantibodies; Autoimmunity; DNA vaccine; Heat-shock protein